2018
DOI: 10.21037/jtd.2018.03.47
|View full text |Cite
|
Sign up to set email alerts
|

Right anterior mini-thoracotomy vs. conventional sternotomy for aortic valve replacement: a propensity-matched comparison

Abstract: Our experience shows that mini-access isolated aortic valve surgery is a reproducible, safe and effective procedure with similar outcomes and no longer operative times compared to conventional sternotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
3
27
2
1
Order By: Relevance
“…[4][5][6] Randomised data looking at the potential benefits of mini-thoracotomy AVR are still awaited; however, some observational studies have shown that this holds a promise. 7,8 When it comes to minimally invasive mitral valve repair, the results of a critical randomised controlled trial are still awaited. 9 Nevertheless, there is a general agreement in the literature, that hard end-points such as short-and long-term survival after MICS are the same with the two techniques.…”
Section: Overviewmentioning
confidence: 99%
“…[4][5][6] Randomised data looking at the potential benefits of mini-thoracotomy AVR are still awaited; however, some observational studies have shown that this holds a promise. 7,8 When it comes to minimally invasive mitral valve repair, the results of a critical randomised controlled trial are still awaited. 9 Nevertheless, there is a general agreement in the literature, that hard end-points such as short-and long-term survival after MICS are the same with the two techniques.…”
Section: Overviewmentioning
confidence: 99%
“…Although the 3F Enable valve is no longer marketed, it was used in only 5.8% of all procedures in this analysis, and its inclusion would be unlikely to alter the findings reported here. These results are important for the modern cardiac surgeon as there is increasing demand from patients and the medical community for minimally invasive surgical approaches, particularly as these have demonstrated reductions in pain and cosmesis (21-23), while still being able to provide the same peri-operative and short term results of SAVR (24)(25)(26)(27). As treatment options increase along with patient complexity, the incorporation of a heart team into the decision making model regarding patients' suitability for surgery will help identify the most appropriate procedure on a case-by-case basis (28).…”
Section: Study 5 Study 15mentioning
confidence: 99%
“…POAF is linked to significant increases in hospital LOS (46), and patients who do not revert to sinus rhythm have increased risk of stroke and long-term mortality. Studies examining links between CPB and CC times in MiAVR cohorts have shown trends towards lower rates of POAF (27,47). This trend is amplified with the use of a sutureless valve via a minimally invasive incision, which further reduces CPB and CC times as well as POAF rates (5,48).…”
Section: Study 5 Study 15mentioning
confidence: 99%
“…Although right anterior mini-thoracotomy (RAMT) outcomes depend on mastering MIAVR techniques, they benefit both from advancements in cardiopulmonary bypass (CPB) techniques and from the utilization of videothoracoscopic assistance; the latter adds considerable benefit to performance and procedural safety, bringing a reduction in cross-clamp times, CPB times, and ventilator support, and shorter intensive care and total hospital time [3][4][5].…”
Section: Introductionmentioning
confidence: 99%